2007
DOI: 10.3201/eid1312.070343
|View full text |Cite
|
Sign up to set email alerts
|

Seroconversion in Wild Birds and Local Circulation of West Nile Virus, Spain

Abstract: A serosurvey for neutralizing antibodies against West Nile virus (WNV) in common coots (Fulica atra) was conducted in Doñana, Spain. Antibody prevalence was highest in 2003, intermediate in 2004, and lowest in 2005. Some birds seroreverted <1 year after first capture. Seroconversion of birds suggests local circulation of the virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 10 publications
5
55
0
Order By: Relevance
“…The specificity of the VNT employed in our study has been analyzed previously using a panel of sera with specificity for different flaviviruses (WNV, yellow fever virus, dengue virus, and tick-borne encephalitis virus), and titers of 10 or higher were only detected in sera from WNV-infected individuals (Figuerola et al 2007a). Additionally, previous studies have shown a higher specificity to WNV in neutralization tests run in parallel against Usutu virus (another bird Flavivirus), confirming that the flavivirus causing the immune reaction is more closely related to WNV than to other flaviviruses (Figuerola et al 2007b). Each species was scored as resident, short-distance migrant (wintering in southern Europe or in Africa north of the Sahara), or trans-Saharan migrant (long-distance migrants wintering south of the Sahara) as per Cramp and Perrins (1994).…”
Section: Methodssupporting
confidence: 50%
“…The specificity of the VNT employed in our study has been analyzed previously using a panel of sera with specificity for different flaviviruses (WNV, yellow fever virus, dengue virus, and tick-borne encephalitis virus), and titers of 10 or higher were only detected in sera from WNV-infected individuals (Figuerola et al 2007a). Additionally, previous studies have shown a higher specificity to WNV in neutralization tests run in parallel against Usutu virus (another bird Flavivirus), confirming that the flavivirus causing the immune reaction is more closely related to WNV than to other flaviviruses (Figuerola et al 2007b). Each species was scored as resident, short-distance migrant (wintering in southern Europe or in Africa north of the Sahara), or trans-Saharan migrant (long-distance migrants wintering south of the Sahara) as per Cramp and Perrins (1994).…”
Section: Methodssupporting
confidence: 50%
“…Serum samples were not available from local birds but no abnormal bird deaths were observed. It is possible that WNV had been introduced by migratory birds and then amplified in local bird populations as described in other countries (Zeller and Schuffenecker, 2004;Schuffenecker et al, 2005;Figuerola et al, 2007;Gangoso et al, 2010). Formal evidence for introduction of WNV in the country by migratory birds will require a search for acute infection during migration.…”
Section: Discussionmentioning
confidence: 99%
“…A primary role of migratory birds in WNV introduction, reintroduction, and spread across Europe [135][136][137][138][139] and the Americas [140,141] is well documented. However, comparison of the levels of neutralizing antibodies in migratory and resident birds in the south of Spain [135,136] , the seroconversion observed in some recaptured resident birds of the same area [137] , and the significant number of positive resident birds found in Great Britain [142] and Italy [143] support that there is also local circulation of the virus.…”
Section: Ecologymentioning
confidence: 99%
“…However, comparison of the levels of neutralizing antibodies in migratory and resident birds in the south of Spain [135,136] , the seroconversion observed in some recaptured resident birds of the same area [137] , and the significant number of positive resident birds found in Great Britain [142] and Italy [143] support that there is also local circulation of the virus. Contribution of resident birds to the initiation of annual infection cycles in the USA has also been suggested [144] .…”
Section: Ecologymentioning
confidence: 99%